The Use of AI in Accounting Students' Face-to-Face Discussions: Dimensions of Legality, Ethics, and Behavior (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2024)
Ethics in face-to-face discussion learning for accounting students finds new challenges when AI has been widely used. This study aims to determine the dimensions of legality, ethics, and behavior of AI use in accounting students' discussions. This study is exploratory descriptive. Primary data were collected through interview methods. Secondary data was obtained through a literature study. Respondents were 3rd-semester students of the accounting study program who had not taken the Professional Ethics course. The findings from the legal aspect show that there is a legal vacuum related to the results of AI's work. Therefore, the results of AI's work are owned by users who download it and agree to the terms and conditions that apply to the AI ​​installed on their devices. In this regard, we recommend the implementation of the Work Made For Hire Doctrine. The Ethics Aspect is still related to the legal vacuum aspect, so students need rules or initial agreements in using AI in face-to-face discussion activities. The result strengthens the evidence of deontological ethics in Accounting students. The benefits of using AI from the results of this study are to increase class activity, so that lecturers are expected to elaborate on the use of AI in their lecture methods. Another positive side of using AI is because the answers are too broad and often inconsistent, this condition triggers students’ critical thinking. On the other hand, students generally use AI to save time. Therefore, it is recommended that accounting student lecturers provide a different perspective on the importance of studying lecture material, and emphasize the assessment of each individual based on the process, not on the result.